Chromosome‐level genome assembly of the predator Propylea japonica to understand its tolerance to insecticides and high temperatures. (28th October 2019) - Zhang, Lijuan; Li, Song; Luo, Junyu; Du, Pei; Wu, Linke; Li, Yarong; Zhu, Xiangzhen; Wang, Li; Zhang, Shuai; Cui, Jinjie
Abstract: The ladybird beetle Propylea japonica is an important natural enemy in agro‐ecological systems. Studies on the strong tolerance of P. japonica to high temperatures and insecticides, and its population and phenotype diversity have recently increased. However, abundant genome resources for obtaining insights into stress‐resistance mechanisms and genetic intra‐species diversity for P. japonica are lacking. Here, we constructed the P. japonica genome maps using Pacific Bioscience (PacBio) and Illumina sequencing technologies. The genome size was 850.90 Mb with a contig N50 of 813.13 kb. The Hi‐C sequence data were used to upgrade draft genome assemblies; 4, 777 contigs were assembled to 10 chromosomes; and the final draft genome assembly was 803.93 Mb with a contig N50 of 813.98 kb and a scaffold N50 of 100.34 Mb. Approximately 495.38 Mb of repeated sequences was annotated. The 18, 018 protein‐coding genes were predicted, of which 95.78% were functionally annotated, and 1, 407 genes were species‐specific. The phylogenetic analysis showed that P. japonica diverged from the ancestor of Anoplophora glabripennis and Tribolium castaneum 236.21 million years ago. We detected that some important gene families involved in detoxification of pesticides and tolerance to heat stress were expanded in P. japonica, especially cytochrome P450 and Hsp70 genes. Overall, the high‐quality draft genome sequence of P. japonica will provide invaluable resource for understanding the molecular mechanisms of stress resistance and will facilitate the research on population genetics, evolution and phylogeny of Coccinellidae. This genome will also provide new avenues for conserving the diversity of predator insects.